2014
DOI: 10.1039/c4ra06485b
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion ionic liquid membranes (EILMs) for removal of Pb(ii) from aqueous solutions

Abstract: Ionic liquids (ILs) are playing increasingly important roles in the membrane separation processes. The present manuscript discusses the removal of Pb(II) ions from aqueous solution using an emulsion ionic liquid membrane (EILM) process. Initially, the emulsion liquid membrane (ELM) was prepared by stirring strip phase (sulphuric acid) and organic phase (surfactant: span 80, extractant: D2EHPA, diluent: hexane) together under high speed agitation. Note that, the parameters of the ELM process such as emulsificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 33 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that various ions can be successfully extracted by ELM. [18][19][20][21][22][23] Few papers have been reported on the extraction of lanthanides by ELM. [24][25][26] Teramoto et al 27 and Tang and Wai 28 explored the extraction and transport of trivalent lanthanides by liquid membrane systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that various ions can be successfully extracted by ELM. [18][19][20][21][22][23] Few papers have been reported on the extraction of lanthanides by ELM. [24][25][26] Teramoto et al 27 and Tang and Wai 28 explored the extraction and transport of trivalent lanthanides by liquid membrane systems.…”
Section: Introductionmentioning
confidence: 99%
“…A multiple emulsion with an internal phase (NaOH; MgSO 4 ), organic phase (Parleam 4; Abil EM90), and external phase (Lutrol F127) has been reported as a relatively efficient and safe treatment in vitro for paraquat poisoning . In fact, in view of the large specific surface areas and high selectivity, the technique of emulsion with organic surfactants has been investigated in many fields such as (i) the removal of metal ions and recovery of organics in waste, (ii) the controlled release of drugs, and (iii) the removal of toxins from organisms . Nevertheless, because of the poor thermodynamic stability, probable toxicity, and low biocompatibility, such emulsions containing organic surfactants have limited applications, especially in pharmacy and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Lead contamination in an environment is a very important problem worldwide due to its highly toxic and nonbiodegradable nature [1]. The industrialized activities using lead such as batteries, photographic materials, pigments, fuels and explosives have contaminated the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Various destructive effects have been found as a result of heavy metal pollution. Therefore, a limit of 0.01 ppm for Pb in the surface water was recognized by WHO and USEPA [1]. There are several methods for treating Pb discharges such as smelting [2], adsorption [3], ion exchange [4], and liquid-liquid extraction [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation